THE EFFECT OF TALKING STICK METHOD ON STUDENTS’ VOCABULARY MASTERY AT THE SEVENTH GRADE OF SMP SWASTA DARUSSALAM MEDAN - Citra Purwira Sari Br. Sara'an; Ashari P. Swondo (Universitas Potensi Utama, 2021)
This Study was aimed to find the empirical proof of The Effect Talking Stick Method Students’ Vocabulary Mastery by using Talking Stick. The method that was a quantitative method. The design of this study was experimental study. This study was 60 students of seventh grade. The instrument of this study was test. The tets were divided into two, there were pre-test and post-test. The data that were obtained from test analyzed by using SPSS statistic 25 program. The result of the study showed that the mean score of post-test in control class was 68.50 while the mean score of post-test in experiment class was 85.33. Based on the criteria of hypothesis test that if sig. 2 tailed (p) was lower than alpha (α) 0.05, the Ho(Null Hypothesis) was rejected and Ha (Alternative Hypothesis) was accepted. In this study, the result of sig. 2 tailed was 0.000 and it proved that p<α . It showed that there was a significant to Talking Stick Method Students’ Vocabulary Mastery